Influence of individual life course and neighbourhood socioeconomic position on dietary intake in African Americans: the Jackson Heart Study. Issue 3 (12th March 2019) - Gao, Yan; Hickson, DeMarc A; Talegawkar, Sameera; Norwood, Arnita Ford; Tucker, Katherine L; Sims, Mario; Diez Roux, Ana V; Griswold, Michael
Abstract : Objective: African Americans, especially those in the Southeastern USA, have different dietary behaviours from the general US population, and have the highest prevalence, incidence and mortality of diet-related disease outcomes, such as cardiovascular disease. However, there are scant data regarding factors such as socioeconomic position (SEP) across the life course that influence dietary behaviours in this high-risk population. Our aim was to examine the impact of life course and neighbourhood SEPs on dietary intake among African Americans. Participants and setting: Data for this cross-sectional analysis came from the community-based Jackson Heart Study (JHS). We analysed a total of 3948 JHS participants (mean age: 55.4±12.5; 63.9% women), who had complete dietary intake and covariate information. Methods: We examined the associations of childhood SEP (CSEP), adulthood SEP (ASEP) and neighbourhood SEP (NSEP) with 10 selected dietary intake measures, using multilevel log-gamma generalised linear regression models. Outcome measures: Dietary intake measures include daily saturated fat, sodium, protein, fibre, fruits and vegetables, whole grains, sugar-sweetened beverage, nuts, fish and processed meat. Results: In age, sex and total energy intake adjusted models, most dietary intakes were associated with these three SEP measures. After additional adjustment for other SEP measures, most of the significant associations with CSEP and NSEP were attenuated, except for the associations of fibre with CSEP (relative rate [RR] [95% CI] 1.05 [1.00–1.10]) and whole grains with NSEP (RR [95% CI] 1.28 [1.02–1.61]). The associations (shown as RR [95% CI]) between ASEP and sugar-sweetened beverage: 0.70 (0.59–0.83), processed meat: 0.75 (0.63–0.90), sodium: 0.99 (0.94–1.00), fibre: 1.10 (1.03–1.16), protein: 1.05 (1.01–1.09), fruits and vegetables: 1.21 (1.11–1.32), nuts: 2.13 (1.59–2.87), and fish: 1.57 (1.27–1.95) generally persisted after additional adjustment for both CSEP and NSEP. However, the association between ASEP and whole grains was attenuated. Conclusions: High ASEP may have a more beneficial influence on dietary practices in African Americans than CSEP or NSEP.